Incentives to Comply with the Minimum Wage in the US and UK - Anna Stansbury (Institute of Labor Economics (IZA), 2024)
There is substantial evidence of minimum wage noncompliance in the US and the UK. In this paper, I compile new, comprehensive data on the costs minimum wage violators incur when detected. In both countries, the costs violators face upon detection are often little more than the money they saved by underpaying. To have an incentive to comply under existing penalty regimes, typical US firms would thus have to expect a 47%-83% probability of detection by the DOL, or a 25% probability of a successful FLSA suit. In the UK, typical firms would have to expect a 44%-56% probability of detection. Actual probabilities of detection are substantially lower than this for many firms, and would likely remain so even with realistic increases in enforcement capacity. Improved enforcement alone is thus insufficient: expected penalties must also substantially increase to ensure that most firms have an incentive to comply.
Keywords: J38; J58; K31; 330; minimum wage; labor standards; compliance and enforcement; industrial relations